PENINGKATAN KUALITAS HIDUP LANSIA MELALUI PEMBERDAYAAN LANSIA PRODUKTIF, GAYA HIDUP SEHAT, DAN AKTIF - Munazar Munazar; Halimatussakdiah Halimatussakdiah; Baharuddin Baharuddin (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Health issues that need to be addressed immediately are health services for the elderly, especially the prevention of non-communicable diseases that can reduce the quality of life of the elderly, such as heart and blood vessel disease, cancer, COPD, and diabetes. In the village of Lhok Rameuan, 12 cases of hypertension and 15 cases of diabetes were found among the elderly. Another problem is the lack of participation of health cadres in addressing health issues among the elderly. This community service program aims to improve the quality of life of the elderly through the empowerment of productive elderly people, healthy and active lifestyles, by activating health cadres, and empowering the elderly themselves. The methods implemented were counseling, health checks, and exercise for the elderly. The results of the community service showed that the empowerment of the elderly had increased and health cadres were playing a greater role in improving the health of the elderly. These results indicate that follow-up is needed to improve the quality of life of the elderly through the empowerment of productive elderly people and a healthy and active lifestyle by families, community health centers, and other relevant agencies